A Comparison of Pain Assessment Measures in Pediatric Sickle Cell Disease. Issue 3 (April 2015) - Myrvik, Matthew P.; Drendel, Amy L.; Brandow, Amanda M.; Yan, Ke; Hoffmann, Raymond G.; Panepinto, Julie A.
<x xml:space="preserve">Abstract</x> Given the availability of various pain severity scales, greater understanding of the agreement between pain scales is warranted. We compared Visual Analog Scale (VAS) and Numeric Rating Scale (NRS) pain severity ratings in children with sickle cell disease (SCD) to identify the relationship and agreement between pain scale ratings. Twenty-eight patients (mean±SD age, 14.65±3.12 y, 50% female) receiving pain interventions within the emergency department completed serial VAS and NRS pain severity ratings every 30 minutes. Data were used to calculate the relationship (Spearman correlation) and agreement (Bland-Altman approach) between the VAS and NRS. One hundred twenty-eight paired VAS-NRS measurements were obtained. VAS and NRS ratings were significantly correlated for the initial assessment (rs=0.88, P<0.001) and all assessments (rs=0.87, P<0.001). Differences between VAS and NRS means were −0.52 (P=0.006) for the initial assessment and −0.86 (P<0.001) across all assessments. The difference between VAS and NRS ratings decreased as pain severity increased across all assessments (P=0.027), but not the initial assessment. Within pediatric patients with SCD, VAS and NRS ratings were found to trend together; however, VAS scores were found to be significantly lower than NRS scores across assessments. The agreement between the 2 measures improved at increasing levels of pain severity. These findings demonstrate that the VAS and NRS are similar, but cannot be used interchangeably when assessing self-reported pain in SCD.